N-terminal propeptide of type III procollagen for predicting diastolic dysfunction in patients with myocardial infarction and preserved ejection fraction - A. V. Osokina; V. N. Karetnikova; O. M. Polikutina; A. V. Ivanova; O. E. Avramenko; O, V. Gruzdeva; O. L. Barbarash (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To study changes in the level of fibrotic scarring marker — the N-terminal propeptide type III procollagen (PIIINP) and structural and functional parameters with the assessment of diastolic function in patients a year after ST segment elevation myocardial infarction (STEMI) and preserved left ventricle (LV) contractility.Material and methods. At first, the study included 120 (100%) STEMI patients. Next, patients with an LV ejection fraction (EF) ≥50% were selected. The final analysis included 86 STEMI patients. Upon hospitalization, the patients underwent routine diagnostic tests, coronary angiography with stenting of culprit artery. Echocardiography and determination of venous blood PIIINP and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels was on the 1st (time point 1) and 12th day (time point 2) of disease and after a year (time point 3). To compare the obtained values of fibrotic scarring markers, a control group was formed, including 20 (100%) healthy volunteers, identical in age and sex with the studied sample.Results. On the first day of MI, 25 (29,1%) patients with signs of diastolic dysfunction (DD) were identified among those with preserved LVEF. After 1 year, the number of such patients increased by 10% (n=9). Initially increased (relative to the control group) concentration of PIIINP on the first day (311,2 [220,1; 376,3] ng/ml) decreased by the 12th day (223,3 [195,3; 312,1] ng/ml) and returned to the initial values a year after the MI (312,6 [228,0; 383,8] ng/ml). The NT-proBNP concentration during the hospitalization period did not exceed the reference values and did not differ between 1 and 2 time points (p=0,127). One year later, the NT-proBNP concentration significantly exceeded the values of the previous determinations and amounted to 124,4 pg/ml (p=0,043). According to the ROC analysis, with a PIIINP ≥387,8 ng/ml on the first day, the risk of DD increases (p=0,050, sensitivity, 84,62%, specificity, 55,56%) within a year after STEMI with preserved LVEF.Conclusion. The threshold of PIIINP (≥387,8 ng/ml) was established for the first day of MI, at which the risk of DD increases one year after the index event. An increase in NT-proBNP concentration one year after STEMI indicates the progression of heart failure.